2011
DOI: 10.1038/477271a
|View full text |Cite
|
Sign up to set email alerts
|

Should fracking stop?

Abstract: CORRESPONDENCE Pros and cons of 24/7 working stir up debate p.280 CULTURE Martin Kemp muses on 15 years of artists in lab schemes p.278 MUSIC In conversation with climate-change composer Paul D. Miller p.279 HISTORY Copernicus biography from Dava Sobel mixes fact and fiction p.276 Natural gas from shale is widely promoted as clean compared with oil and coal, a 'win-win' fuel that can lessen emissions while still supplying abundant fossil energy over coming decades until a switch to renewable energy sources is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
256
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(259 citation statements)
references
References 5 publications
1
256
0
2
Order By: Relevance
“…These concerns include changes in air quality (6), human health effects for workers and people living near well pads (5), induced seismicity (7), and controversy over the greenhouse gas balance (8,9). Perhaps the biggest health concern remains the potential for drinking water contamination from fracturing fluids, natural formation waters, and stray gases (4, 10-12).…”
mentioning
confidence: 99%
“…These concerns include changes in air quality (6), human health effects for workers and people living near well pads (5), induced seismicity (7), and controversy over the greenhouse gas balance (8,9). Perhaps the biggest health concern remains the potential for drinking water contamination from fracturing fluids, natural formation waters, and stray gases (4, 10-12).…”
mentioning
confidence: 99%
“…The potential constraints from environmental issues are not included. Taking shale gas as an example, extracting shale gas may result in many environmental problems, including methane emissions, water use, water pollution, and induced earthquakes (Howarth and Ingraffea 2011;Entrekin et al 2011;Frohlich 2012). Among these, water issues may be the most significant constraining factor for China shale's gas development.…”
Section: Non-conventional Gas Productionmentioning
confidence: 99%
“…The interaction between abundant natural gas and greenhouse gas mitigations policies is another issue in need of further examination 9,10 . Finally, we note that the global deployment of improved natural gas extraction technology carries implications not only for climate change, but also for many other important concerns including air and water quality, energy security, access to modern energy, and economic growth 1,2,8 .…”
Section: Research Lettermentioning
confidence: 99%
“…Some researchers have observed that abundant natural gas substituting for coal could reduce carbon dioxide (CO 2 ) emissions [3][4][5][6] . Others have reported that the non-CO 2 greenhouse gas emissions associated with shale gas production make its lifecycle emissions higher than those of coal 7,8 . Assessment of the full impact of abundant gas on climate change requires an integrated approach to the global energyeconomy-climate systems, but the literature has been limited in either its geographic scope 9,10 or its coverage of greenhouse gases 2 .…”
mentioning
confidence: 99%